2001
DOI: 10.1152/jn.2001.85.5.1823
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Equivalence of Somatosensory Areas I and II for Tactile Processing in the Cerebral Cortex of the Marmoset Monkey

Abstract: Responsiveness of the first somatosensory area (SI) of the cerebral cortex was investigated in the marmoset monkey (Callithrix jacchus) in association with cooling-induced, reversible inactivation of the second somatosensory area, SII. The aim was to determine whether SI responsiveness to peripheral tactile stimulation depends on SII and therefore whether SI and SII in the marmoset occupy hierarchically equivalent positions in a parallel organizational scheme for thalamocortical tactile processing as appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
(116 reference statements)
5
39
0
1
Order By: Relevance
“…Retrograde degeneration methods also indicated that VP neurons connect directly to both S1 and S2 in cats and squirrel monkeys (Jones, 1975;Stevens et al, 1993). Finally, cooling of S1 does not change S2 responsiveness to peripheral stimulation in rabbits, opossums, rats, and marmoset monkeys (Murray et al, 1992;Coleman et al, 1999;Heppelmann et al, 2001;Zhang et al, 2001b). These results provide an alternative view, that is, S2 received direct thalamic inputs rather than through a serially organized path by means of S1.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Retrograde degeneration methods also indicated that VP neurons connect directly to both S1 and S2 in cats and squirrel monkeys (Jones, 1975;Stevens et al, 1993). Finally, cooling of S1 does not change S2 responsiveness to peripheral stimulation in rabbits, opossums, rats, and marmoset monkeys (Murray et al, 1992;Coleman et al, 1999;Heppelmann et al, 2001;Zhang et al, 2001b). These results provide an alternative view, that is, S2 received direct thalamic inputs rather than through a serially organized path by means of S1.…”
mentioning
confidence: 77%
“…S1 and S2 hierarchies have been studied by inactivation strategies in many species. Functionally, S2 seemed to be equivalent with S1, because it maintained its responsiveness when S1 was reversibly inactivated in rabbits, opossums, prosimian primates, tree shrews, marmoset monkeys, and rats (Woolsey and Wang, 1945;Garraghty et al, 1991;Murray et al, 1992;Coleman et al, 1999;Heppelmann et al, 2001;Zhang et al, 2001b). When the treatment was reversed in cat and marmoset monkey studies, S1 was similarly found to maintain its responsiveness after S2 inactivation (Turman et al, 1995;Zhang et al, 2001b).…”
Section: Thalamic Coactivation Of S1 and S2mentioning
confidence: 99%
“…SII directly connects not only with the ventral posterior nucleus of the thalamus (37,38), but also with SI in nonhuman primates (39). Electrical stimulation of the human median nerve causes synchronized activity in the neurons of SII contralaterally 20 -30 msec after stimulation, which is coincident with the first responses generated in SI (40).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, connections between S1 and S2 have never been directly examined, but such connectivity has been inferred previously based on the latency difference between the somatosensory-evoked fields (SEFs) from S1 and the S2 region as measured using EEG and MEG recordings (see Lin and Forss 2002 for a review). Although there is increasing evidence for parallel processing in the somatosensory system (Karhu and Tesche 1999;Zhang et al 1996Zhang et al , 2001, support for serial processing between primary and secondary somatosensory fields comes from neuroanatomical studies of connectivity, cortical deactivation studies, and MEG studies in macaque monkeys and humans (Bohlhalter et al 2002;Felleman and Van Essen 1991;Garraghty et al 1990;Inui et al 2004;Pons et al 1992). More recent studies have shown that although both S2 and PV receive afferents from areas 3b and 1, which process cutaneous inputs, and from area 3a, which processes inputs from proprioceptors (Disbrow et al 2003;Qi et al 2002), they also project to posterior parietal areas (Disbrow et al 2003), including cortex representing the hands in the anterior intraparietal sulcus (AIP) (Lewis and Van Essen 2000).…”
Section: Serial Processing and Sensorimotor Integrationmentioning
confidence: 99%